The INQUA Dunes Atlas chronologic database. (29th July 2016) - Lancaster, Nicholas; Wolfe, Stephen; Thomas, David; Bristow, Charlie; Bubenzer, Olaf; Burrough, Sallie; Duller, Geoff; Halfen, Alan; Hesse, Paul; Roskin, Joel; Singhvi, Ashok; Tsoar, Haim; et al.
Abstract: The INQUA Dunes Atlas project has developed a global digital database of chronological information for periods of inland or continental sand dune accumulation and stabilization. The database comprises information on the site location (including coordinates), dune type, and stratigraphic context, pertinent analytical information (e.g. luminescence procedures), and literature citations to the original data source. This paper discusses the background to the project, the concept and structure of the chronologic database that forms its core, and gives some examples of the scope of the database and ways in which it can contribute to greater understanding of the spatial and temporal variability in dune development.